2016
DOI: 10.1186/s40064-016-3073-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern and analysis of plasmid profiles of Pseudomonas aeruginosa from human, animal and plant sources

Abstract: Multidrug resistant organisms (MDROs) constitute a major public health threat globally. Clinical isolates of Pseudomonas aeruginosa remains one of the most studied MDROs however there is paucity of information regarding the susceptibility of its animal and plants isolates to antipseudomonas drug in Nigeria. From a total of 252 samples consisting of plants, animals and clinical samples, 54, 24 and 22 P. aeruginosa were isolated from vegetables, animals and clinical sources respectively. All the isolates were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
6
22
1
1
Order By: Relevance
“…Similar findings elsewhere reported a plasmid prevalence rate of 36.4% [33]. Plasmids are mobile genetic elements and can also facilitate the dispersal of resistance genes among the bacterial population and can also serve as vehicle for other resistance mechanisms [34]. The mobility characteristic of an extrachromosomal DNA means that plasmids can be easily acquired or lost, in both in vivo and in vitro conditions [35].…”
Section: Resultssupporting
confidence: 67%
“…Similar findings elsewhere reported a plasmid prevalence rate of 36.4% [33]. Plasmids are mobile genetic elements and can also facilitate the dispersal of resistance genes among the bacterial population and can also serve as vehicle for other resistance mechanisms [34]. The mobility characteristic of an extrachromosomal DNA means that plasmids can be easily acquired or lost, in both in vivo and in vitro conditions [35].…”
Section: Resultssupporting
confidence: 67%
“…This category included 42 studies, with the inclusive eligibility criteria in which diverse phenotypic or genotypic methods were utilized ([14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], Tables S1–S3). These studies sought to detect the presence and extent of AMR in collected samples with a selected panel of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The 80 studies excluded did not directly relate to the objectives or yielded information that could be subjected to organized peer review and data analysis. The 59 included studies were sorted into three categories of 42 antimicrobial resistance studies [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], 16 antimicrobial residue studies [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], and 1 antiseptic or disinfectants study [72]. The PRISMA-style flowchart was modified and used for this analytical review (Figure S1) [73].…”
Section: Methodsmentioning
confidence: 99%
“…Elsayed et al (2016) reported recovery of P. aeruginosa isolates from 22.89% broiler samples in Egypt. Similarly, Odumosu et al (2016) also recovered P. aeruginosa isolates from 39.68% samples from cow, poultry, clinical samples and vegetables from Nigeria. Confirmation with BD ™ Phoenix bacterial identification system as well as 16S rRNA gene based PCR may be the reason behind the report of present study depicting lower occurrence of P. aeruginosa.…”
Section: Detection Of Biofilm Associated Genes Virulence Genes and Amentioning
confidence: 88%